Effects of Ginseng and Echinacea on Cytokine mRNA Expression in Rats - Deniz Uluışık; Ercan Keskin (The Scientific World Journal)
The aim of the study was to determine the effect of ginseng and echinacea on the mRNA expression of IL-10, TNF-α, and TGF-β1 in healthy rats. Six-week-old male Fischer 344 rats (n=48) were used. The animals were divided into three equal groups, as follows: control (C); ginseng (G); echinacea (E). While the C group was fed a standard rat diet (Purina) ad libitum for a period of 40 days, the G and E groups animals received the same diet containing 0.5 g/kg of Panax ginseng root powder and 0.75 g/kg of Echinacea purpurea root powder, respectively. Blood samples were obtained from 8 rats in each group after 20 and 40 days of treatment, and the mRNA expression of IL-10, TNF-α, and TGF-β1 was determined. After 20 days of treatment, the expression of IL-10 mRNA in the G group was different from the C group (P<0.05); however, after 40 days of treatment, there was no difference between the groups. There was no difference after 20 and 40 days of treatment between the groups with respect to the expression of TGF-β1 mRNA. After 20 days of treatment, the expression of TNF-α mRNA in the E group was higher (P<0.05) than the C group. After 40 days of treatment, the expression of TNF-α mRNA was similar in all of the groups. Based on the current study, the increase in expression of IL-10 mRNA in the G group and the increase in expression of TNF-α mRNA in the E group support the use of these plants for purposes of modulating the immune system. However, a more detailed study regarding the effects of ginseng and echinacea on these cytokines and other cytokines is needed.